(3eaJGM GdRQjI aj EYJbGO GdSGOI GdUhajIs - (3YHO GdhgGH Hf CMeO Hf Ydj GdnMnfaj, fSHg Edi eMeO GHf GdMfajI, GdTYQGfj, CHh eMeO , J (B973 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHYO agPg YbjOI TQjaI EfbOMJ di ef JUaM YHGQGJ GdChdjGA GdeMbbjf hcGdTjN eMi GdOjf Hf GdYQHi heQLYgG cdgG Edi GdejRGf GdBJi PcQg ChGNQ GdcJGH s
(3BNQgG (B:s
(3aJMaX jG CNj ef JLQjM YbGFO CMO ef GdeSdejf , hGMe SeYc hdSGfc hbdHc hdG JMce HNQhL CMO ef GdESdGe hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3HChdgG hbajI HGSe YdGeI HjQhJ GdTjN eMeO SYjO Hf eMeO Hc EjGS GdOeTbieDQNI SfI (B1373(3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B180s
Keywords: (3GdJUha hGdBOGH GdTQYjIs